2017
DOI: 10.1002/hpm.2482
|View full text |Cite
|
Sign up to set email alerts
|

Do health care reforms in Turkey have a significant effect in equal access to maternal and child health services in Turkey: An evidence from 20 years

Abstract: This study aimed to investigate whether there was an improvement in the equitable access to maternal and child health care services by examining the effects of socioeconomic and individual factors in Turkey from 1993 to 2013 and determine the effectiveness of health care reforms implemented mainly under the Health Transformation Program since 2003 on equitable access t;o maternal and child health care services in terms of years. The study used nationally representative 5 Turkey Demographic and Health Surveys (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…7 In another study that uses province-level data, researchers found that primary health care use for all ages improved following the introduction of FM. 15 Analysis has also been conducted based on comparisons of health services utilization probabilities 16,17 and equity in health care use 18 before and after FM was implemented, referring to the improvements in utilization in the post-FM period.…”
Section: Literature Reviewmentioning
confidence: 99%
“…7 In another study that uses province-level data, researchers found that primary health care use for all ages improved following the introduction of FM. 15 Analysis has also been conducted based on comparisons of health services utilization probabilities 16,17 and equity in health care use 18 before and after FM was implemented, referring to the improvements in utilization in the post-FM period.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition to improving the health level and efficiency, equality has increasingly become one of the main goals of health reform efforts around the world [ 1 ]. Health service utilization is an interactive point between health care users and the health care system, and its equality is the basis for realizing health equity and one of the important indicators for evaluating the effectiveness of health services.…”
Section: Introductionmentioning
confidence: 99%
“…In children, healthier eating habits can support better academic performance [6,30]. Moreover, child health is shown as an important indicator of the lifespan and life quality, as well as the economic development of a country [6,30,31].…”
Section: Introductionmentioning
confidence: 99%